Pengaruh kepimpinan karismatik pengetua ke atas motivasi guru - Norlela, Ali (2011)
This study aimed to investigate the influence of the charismatic leadership of the principal on teachers' motivation at Simunjan secondary schools, In addition, the study also to determine the differences of teachers' motivation level based on gender and teaching experience. A total of 100 teachers from four secondary schools at district Simunjan randomly selected in this study. A cross-sectional survey design and standardized questionnaires were utilized in this study. Conger-Kanungo Scale of Charismatic Leadership by Conger et al. (1997) was used to measure charismatic leadership of principals and Motives Achievement Scale-Revised (AMS-R) by Lang and Fries (2006) was used to measure teachers' motivation level. Data collected were analyzed using the SPSS software (Statistical Package for the Social Sciences). The statistical analysis used in this study was the t-test, to investigate the difference of motivation level of teachers based on teachers' gender. One way ANOVA was used to test the difference of teachers' motivation level based on teaching experience. Stepwise regression analysis was utilized to test the influence of the principal charismatic leadership on teachers' motivation. Based on data analysis, result showed that the charismatic leadership of the principals have a positive effect on teachers' motivation by 75% (seventy percent was the sensitive to the environmental dimension, and 5.9% was extraordinary behavior dimension. The motivations of teachers' were found to be high but there was no difference of teachers' motivation based on teachers' gender and teaching experience